HAMBATAN PRINSIP RESTORATIVE JUSTICE DALAM PROSES PERKARA PENGANIAYAAN - Arinugroho, Rudy; Santoso, Bambang (Verstek, 2023)
This study describes and examines the what are the obstacles to the principle of restorative justice in the persecution case process based on case file number BP/07/XII/2021/ SEK BYL KT at the Boyolali District Attorney's Office. This research is empirical or sociological legal research of a descriptive nature. Data types include primary data and secondary data. The data collection techniques used are the study of documents or library materials, observations or observations, and interviews or interviews, then the technical analysis used is a qualitative method that produces analytical descriptive data. The results showed that the restorative judiciary in the case file number BP/07/XII/2021/ SEK BYL KT at the Boyolali District Attorney's Office in the abuse case, agreed that the victim forgave the suspect by entering into a peace effort agreement because the victim and the suspect were still related, where the suspect was the grandson of the victim, and the suspect promised not to repeat his actions, and the response from the community in making peace efforts was quite positive. Thus, peace efforts in the case of persecution can be implemented. Keywords : Criminal Persecution, Restorative Justice, Implementation